Physiological and Behavioral Responses to Vocalization Playback in Mice - Niemczura, Alexandra C.; Grimsley, Jasmine M.; Kim, Chae; Alkhawaga, Ahmad; Poth, Austin; Carvalho, Alyssa; Wenstrup, Jeffrey J. (Frontiers in behavioral neuroscience, 2020)
In mice, the caller’s production of social vocalizations has been extensively studied but the effect of these vocalizations on the listener is less understood, with playback studies to date utilizing one vocalization category or listeners of one sex. This study examines how several categories of mouse vocalizations affect listeners of both sexes to better understand the communicative functions of these vocal categories. We examined physiological and behavioral responses of male and female CBA/CaJ mice to playback of four social vocalization categories: ultrasonic vocalizations (USVs), low frequency harmonic calls, mid-frequency vocalizations, and noisy calls. Based on the conditions under which these calls are emitted, we hypothesized that playback of these vocal categories would have differential effects on the listeners. In females, playback of all four vocalization categories increased stress hormone levels (corticosterone), but only the non-USV categories increased corticosterone in males. The magnitude of corticosterone increase in non-USV trials was greater in females than in males. In open field tests, all four vocal categories decreased central ambulation in males and females, indicating an increase in anxiety-related behavior. Further, we found that the proportions of USVs emitted by subjects, but not their overall calling rates, were affected by playback of some vocal categories, suggesting that vocalization categories have different communication content. These results show that, even in the absence of behavioral and acoustic contextual features, each vocal category evokes physiological and behavioral responses in mice, with some differences in responses as a function of the listener’s sex and playback signal. These findings suggest that at least some of the vocal categories have distinct communicative functions.